Intracoronary autologous bone marrow mononuclear cells for the compassionate treatment of advanced heart failure. (25th November 2020) - Jones, D.A; Baca, G.L; Hussain, M; Jardim, V; Davies, L.C; Veerapen, J.V; Martin, J.E; Lowdell, M.V; Mathur, A
Abstract: Background: Intracoronary delivery of autologous bone marrow-derived mononuclear cells (BMCs) has been shown to be beneficial in the treatment of patients with ischaemic (IHD) and non-ischaemic dilated cardiomyopathy (DCM). Given the results of phase II clinical trials in this population, our centre initiated the only programme to offer intracoronary BMCs to patients with advanced heart failure due to IHD or DCM in the UK. Clinical data and outcomes in these patients were maintained as part of a registry, the results of which are reported herein. Purpose: To report outcomes of the first 20 patients with DCM treated at the compassionate stem cell unit. Methods: A total of 45 patients with advanced heart failure (left ventricular ejection fraction (LVEF) at referral of ≤45%, New York Heart Association (NYHA) classification ≥2 and no secondary cause for the cardiomyopathy) despite optimal medical therapy (OMT) were accepted into the programme and received treatment with intracoronary BMCs, manufactured and supplied as Advanced Therapy Medicinal Products, with adjunctive granulocyte colony stimulating factor (G-CSF). All patients received 5 days of G-CSF followed by bone marrow aspiration and IC infusion of cells (∼10ml of BMCs) on Day 6. LVEF was assessed by cardiac CT. Results: Of the 20 patients with DCM, 80% were male with a mean age of 64.6±10.6 years (range 45–81 years old). Baseline LVEF was 36.1%±10.6. Baseline NYHA class distributions were 70% NYHA class II (n=14), NYHA class III 25% (n=5), and NYHA class IV – 5% (n=1). All procedures were performed successfully with no procedural complications (100% radial). One year after treatment, 71.4% of people improved by 1 or more NYHA classes with 28.6% noting no change (1 year NYHA classes I (60%), II (27%) and III (13%)). No patients felt worse. A mean increase of 3.4% (±9.6%) was seen in LVEF at 1 year compared to baseline with a corresponding mean reduction in NT-pro-BNP of 18.9% (mean 1012pmol/l vs 1250pmol/l). In terms of clinical events, at 1 year all treated patients were alive, with no reported MACE events and no admissions for heart failure. Conclusion: IC autologous BMC injections are a novel therapy for patients with advanced HF despite OMT. These data indicate this therapy is safe and results in significant improvement in symptoms of heart failure. An improvement in the LVEF is seen at levels which support initial findings of phase II clinical trials. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Heart Cell Foundation; Barts Heart Centre, St Bartholomew's Hospital